The effect of modal properties of crash box structures with trigger mechanisms towards the crashworthiness by using finite element analysis - Asri, M. N. A. M.; Abdullah, N.A.Z.; M. S. M., Sani (Faculty Mechanical Engineering, UMP, 2021)
In the automotive structure, there are different components that utilise aluminium alloy (AA) sheets and it is used widely in the car body-in-white which comprise bumpers and the crash box structure at the front end of the car which specifically designed to withstand the event of collision. As the structures are also experiencing dynamic loading, it were also a concern for the structures to show satisfied modal properties. In this study, the modal properties of the crash box structures are investigated along with the effect of the modal properties towards the crashworthiness behaviour of the structure itself with the approach of finite element analysis. Experimental modal analysis was also done to further validating the finite element analysis of the modal properties. Three different designs of trigger mechanisms are applied towards the crash box structure to observe on both findings. For the connector element, equivalent nodes of both parts of the crash box structures are used. For the results, the correlation from both findings did show that the presence of trigger mechanism did decreased the magnitude of natural frequencies as well as the mode shape as shown by crash box type 3 by 9.50% and for the crashworthiness output, the crashworthiness behaviour of the crash box with trigger mechanisms were better in term of the collisions phases indicated by the primary peak force and the secondary peak force from the force-displacement curve as also shown by crash box structure type 3 with the percentage of 22.59%. The study does shows that the stiffness and mass distribution due to the presence of trigger mechanism do affect the modal properties of a structure as well as its crashworthiness output.